Juridical analysis of the evidentiary power of the victim's witness statement against the consideration of the acquittal of the crime of defamationn the case of decision number 853/pid.sus/2022/pn.srg - Wiwi, Wiwi; Hendrawati, Sulkiah; Hadi, Hadi Haerul (Journal of Law Science, 2024)
Defamation is an act that harms someone's honor or reputation, as regulated in Article 310 of the Indonesian Penal Code and Article 27 paragraph (3) of Law Number 19 of 2016 on Electronic Information and Transactions (UU ITE). This research analyzes the strength of witness testimony from the victim in defamation cases and considers how judges decide to acquit defendants when the victim is absent from the trial, referring to Law Number 19 of 2016 on Electronic Information and Transactions (UU ITE). The research method used is normative legal research with statutory, case, and conceptual approaches, utilizing secondary data sources consisting of primary, secondary, and tertiary legal materials. The findings indicate that the victim's absence from the trial significantly impacts the strength of evidence, ultimately leading the judge to acquit the defendant. The judge's consideration is also based on the prosecutor's inability to present the victim as a witness to support the indictment, rendering the victim's testimony inadmissible. The conclusion of this study emphasizes that the victim's absence from the trial is a crucial factor affecting the outcome of defamation cases and is a primary consideration for judges in determining the verdict. However, judges should also consider other evidence in making a more comprehensive decision.